PENGARUH MOTIVASI, FASILITAS KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN I PT PANASONIC INDUSTRIAL DEVICE BATAM - sihombing, sanny lastarida; S.E., M.M, Syaifullah (SCIENTIA JOURNAL, 2021)
Human resources are one of the most important aspects in a company. The company will seek to maximize employees to the interests and values of the company in order to improve the well-being of owners and employees. There are several factors that affect human resources, namely motivation and job opportunities, work discipline and performance. The objectives of this study areAnalysis of the impact of work discipline on employee performance (4) Simultaneous analysis of the influence of motivation, employment opportunities and work discipline on employee performance by PT Panasonic Industrial Device Batam. The population of this study are employees of PT Panasonic Industrial Device Batam in Inductor Operator-PCS. The number of samples in this study was 135 using a non-probability sample. The data analysis technique in this study used multiple linear regression analysis, c Lexical Acceptance Test, and Statistical Test. The results showed, among other things: (1) Motivation affects employee performance with the t count> t table (14.324> 1.656); (2) Work facilities affect the performance of employees by the number of t> table (9,599> 1,656); (3) Work discipline does not affect employee performance by counting <t table (0.152 <1.656); (4) Motivation, employment opportunities, and work discipline all affect the performance of employees with a value of Fcount> Ftable (552.730> 2.673). Multiple linear equation Y = -0.683 + 0.496X1 + 0.403X2 + 0.003X3.